Public Service Transformation Based on Local Leadership: A Study in Palleko Village - Idris, Syarif; Sari, Rahma Pramudya Nawang; Azka, Ibnu; Baldan Haramain, Fathur (Ministry of Home Affairs, 2025)
This study aims to analyze the transformation of public services in Palleko Village, Polombangkeng Utara District, Takalar Regency, and the strategies implemented by the Village Head to improve service quality. Effective and efficient public services are very important to meet the needs of the community but are often hampered by various problems such as a complicated bureaucratic system, limited resources, and low community participation. This study uses a qualitative method with a descriptive approach, where data is collected through observation, interviews, and documentation. The results of this study indicate that the Palleko Village Head implements several service transformation strategies, such as improving facilities, providing fair and professional services, and transparency through clear service flow information. Supporting factors in this transformation include the availability of infrastructure, friendly and responsive attitudes from staff, and good relations between the government and the community. However, the main challenges in this transformation process are the professionalism of staff, which still needs to be improved, and the low public awareness of the importance of their role in supporting public services. The transformation of public services in Palleko Village shows that with the right strategy, service quality can be improved so that it is more responsive to community needs and supports inclusive development.